2021
DOI: 10.1002/jia2.25665
|View full text |Cite
|
Sign up to set email alerts
|

Home‐Based Intervention to Test and Start (HITS): a community‐randomized controlled trial to increase HIV testing uptake among men in rural South Africa

Abstract: Introduction The uptake of HIV testing and linkage to care remains low among men, contributing to high HIV incidence in women in South Africa. We conducted the “Home‐Based Intervention to Test and Start” (HITS) in a 2x2 factorial cluster randomized controlled trial in one of the World’s largest ongoing HIV cohorts in rural South Africa aimed at enhancing both intrinsic and extrinsic motivations for HIV testing. Methods Between February and December 2018, in the uMkhanyakude district of KwaZulu‐Natal, we random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Efforts to improve early ART initiation through enhanced HIV testing and linkage to care are critical, as are targeted interventions to boost male engagement with services. Interventions such as community-based multidisease screening [36], patientcentered and personalized services [36], financial incentives [48], and community-based ART initiation and monitoring for men [49] have shown success. While the scalability and sustainability of such interventions are unknown, the need for a holistic approach-such as integrating HIV services with noncommunicable disease services, addressing the wider determinants of health [50], reducing stigma, strengthening the health system including human and other resources, and improving health service quality-alongside more individualized interventions remains.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to improve early ART initiation through enhanced HIV testing and linkage to care are critical, as are targeted interventions to boost male engagement with services. Interventions such as community-based multidisease screening [36], patientcentered and personalized services [36], financial incentives [48], and community-based ART initiation and monitoring for men [49] have shown success. While the scalability and sustainability of such interventions are unknown, the need for a holistic approach-such as integrating HIV services with noncommunicable disease services, addressing the wider determinants of health [50], reducing stigma, strengthening the health system including human and other resources, and improving health service quality-alongside more individualized interventions remains.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples include text-based ART medication reminders and mindfulness exercises to reduce HIV viral load (Table 2). Culturally relevant and gender-specific messaging to engage in HIV prevention [30,101] Loss framed lottery intervention to encourage dual contraception methods to prevent HIV infection [86] HIV to take PrEP medication [142] HIV management Use of priming stimuli that is empowering or culturally meaningful to improve adherence to ART and retention in care [143,144] Use of financial rewards as priming to improve adherence to ART and to suppress viral load count [49,145] Providing safe sex materials as priming to practice safe sex to prevent HIV transmission [146] Personalised cues and reminder messages for remembering dose times to support ART adherence [72,74,147,148] Affect HIV prevention Creating positive emotion for HIV testing or accessing HIV services [111,139,149,150] Peer-led group sessions to learn skills for self-efficacy and positive sexual health behaviours [31] Increasing risk perception towards HIV to encourage HIV prevention behaviours [99,151] HIV management Creating positive emotion for HIV care retention and ART adherence through social, financial, or non-financial support [99,111,143,146] Group sessions targeting positive affect to increase skills for self-efficacy to encourage ART adherence and viral load suppression [146,[152][153][154] Motivational messages to encourage ART adherence [147,150,155] Commitment HIV prevention Use of binding contracts with financial deposits to encourage HIV testing or clinic visits [139,[156]…”
Section: Saliencementioning
confidence: 99%
“…In one study, patients would receive congratulations for attending the clinic three consecutive on-time visits for HIV care, and they were given a sticker to proudly place on an interactive poster publicly displayed in the clinic to celebrate and acknowledge their achievement [143]. Another study involved a multi-component positive affect intervention for MSM who used drugs, eight core skills, and meditation exercises were delivered to them to increase positive affect among HIV management Use of non-explicit commitment devices in the form of financial incentives for ART adherence and viral load suppression goal in the future [108,144,147,154,[169][170][171][172][173][174][175][176][177][178][179][180][181] Use of non-explicit commitment devices in the form of financial incentives to meet HIV testing, linkage to HIV care and clinic attendance goal in the future [172,182,183] Use of non-explicit commitment devices in the form of non-financial incentives for ART adherence and viral load suppression goal in the future [74,147,155] Use of non-explicit commitment devices in the form of non-financial incentives to meet HIV testing, linkage to HIV care and clinic attendance goal in the future [117,143,146,[184][185][186] Ego HIV prevention HIV education sessions alongside financial education programmes to target ego and self-efficacy [18,31,99,[187][188][189] HIV education sessions and peer support to target ego and increase HIV risk perception ...…”
Section: Affectmentioning
confidence: 99%
“…Similar successes were described in another intervention with HIV self-testing targeted to men and young adults in Malawi: 90% of eligible participants accepted HIV testing [ 49 ]. A study in rural South Africa found that home-based testing, coupled with financial incentives, improved uptake of HIV testing among men [ 50 ].…”
Section: Community-based Strategiesmentioning
confidence: 99%